Labor Migration and Economic Growth Nexus in Bangladesh - Rahman, Mohammad Rifat; Rahman, Md. Mufidur; Akter, Roksana (Journal of Accounting, Business and Management (JABM), 2025)
Accelerated globalization and the thirst for economic emancipation of the people create demographic shifts from developing countries to developed countries. To assist policymakers in effective decision making regarding labor migration and economic growth, our paper explores the hidden dynamics between labor migration and economic growth in Bangladesh from 1988 to 2020. The study was developed based on the Auto Regressive Distributed Lag (ARDL) framework to capture long-run and short-run dynamics among the variables. To find the directional relationship, we also perform the Toda Yamamoto Causality test to find the short-run impact on the dependent variables. The existence of co-integration among the variables is demonstrated by the Bounds test result. The empirical results show the long and short-run positive significant relationship between international labor migration and exchange rate. However, Inflation and GDP growth do not have any significant impact on migrant laborers from Bangladesh to abroad. The causality approach indicates a unidirectional causality between labor migration and exchange rate, GDP growth and exchange rate. This paper suggests that the devaluation of the local currency would be a possible way to boost labor export from Bangladesh.